The effect of SiO2 dielectric layer on ultraviolet detecting properties of pentacene thin film transistor - Yakuphanoğlu, Fahrettin; Farooq, W. Aslam (Elsevier Science Sa, 2011)
The pentacene thin film transistor was fabricated on a SiO2/Si substrate by thermal evaporated method at room temperature. Electrical characteristics of the pentacene transistor subjected to a UV light excitation at a wavelength of 365 nm were analyzed. A significant increase in the drain current of the pentacene thin film transistor under a UV excitation of 365 nm is observed with a maximum photosensitivity of 4.51 in the depletion regime. It is concluded that the pentacene thin film transistor can be used in UV photo-detecting devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Thin film transistor; Photoresponse; Field effect mobility